Spatial-temporal genome regulation in stress-response and cell-fate change - Erenpreisa, Jekaterina; Giuliani, Alessandro; Yoshikawa, Kenichi; Falk, Martin; Hildenbrand, Georg Lars; Salmina, Kristine; Freivalds, Talivaldis; Vainshelbaum, Ninel; Weidner, Jonas; Sievers, Aaron; Pilarczyk, Götz; Hausmann, Michael (International journal of molecular sciences, 2023)
Complex functioning of the genome in the cell nucleus is controlled at different levels: (a) the DNA base sequence containing all relevant inherited information; (b) epigenetic pathways consisting of protein interactions and feedback loops; (c) the genome architecture and organization activating or suppressing genetic interactions between different parts of the genome. Most research so far has shed light on the puzzle pieces at these levels. This article, however, attempts an integrative approach to genome expression regulation incorporating these different layers. Under environmental stress or during cell development, differentiation towards specialized cell types, or to dysfunctional tumor, the cell nucleus seems to react as a whole through coordinated changes at all levels of control. This implies the need for a framework in which biological, chemical, and physical manifestations can serve as a basis for a coherent theory of gene self-organization. An international symposium held at the Biomedical Research and Study Center in Riga, Latvia, on 25 July 2022 addressed novel aspects of the abovementioned topic. The present article reviews the most recent results and conclusions of the state-of-the-art research in this multidisciplinary field of science, which were delivered and discussed by scholars at the Riga symposium.